Time-use and academic peer effects in college - Nirav Mehta; Ralph Stinebrickner; Todd R. Stinebrickner (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2018)
This paper examines academic peer effects in college. Unique new data from the Berea Panel Study allow us to focus on a mechanism wherein a student's peers affect her achievement by changing her study effort. Although the potential relevance of this mechanism has been recognized, data limitations have made it difficult to provide direct evidence about its importance. We find that a student's freshman grade point average is affected by the amount her peers studied in high school, suggesting the importance of this mechanism. Using time diary information, we confirm that college study time is actually being affected.
Keywords: 330; Peer effects; Time use; Higher education; Mechanisms